2002
DOI: 10.1038/sj.leu.2402599
|View full text |Cite
|
Sign up to set email alerts
|

Clinical activity of arsenic trioxide for the treatment of multiple myeloma

Abstract: Arsenic has been used since ancient times as a therapeutic agent. However, until recently its use in modern medicine has been restricted to the treatment of a limited number of parasitic infections. In the early 1990s, reports from China described impressive results with arsenic trioxide in patients with de novo, relapsed, and refractory acute promyelocytic leukemia (APL). Other investigators subsequently confirmed these results leading to approval of its use for relapsed or refractory APL in the United States… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
97
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(98 citation statements)
references
References 12 publications
(8 reference statements)
1
97
0
Order By: Relevance
“…In an early clinical trial study, Munshi et al 25 reported that ATO as a single agent was not effective in a phase II study of 11 relapsed/refractory or de novo AML and non-acute promyelocytic leukemia patients. However, only two of these patients had a normal karyotype, and the NPM1 status was not reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In an early clinical trial study, Munshi et al 25 reported that ATO as a single agent was not effective in a phase II study of 11 relapsed/refractory or de novo AML and non-acute promyelocytic leukemia patients. However, only two of these patients had a normal karyotype, and the NPM1 status was not reported.…”
Section: Discussionmentioning
confidence: 99%
“…However, only two of these patients had a normal karyotype, and the NPM1 status was not reported. 25 In a recent clinical trial of ATO alone, one of the seven AML patients of unknown genetic phenotype who were resistant to therapy obtained a complete remission and one a partial remission. 56 In two other clinical studies, the addition of ATO to low-or high-dose cytarabine and idarubicin appeared to improve the complete remission rate, although again NPM1 mutational status was not determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We were interested in magnifying the efficacy of As 2 O 3 using substances that might be transferable to clinical application because the clinical applications of As 2 O 3 gain in importance not only for therapy of relapsed and refractory APL [29,30,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47], but also for treatment of multiple myeloma [48][49][50], myelodysplastic syndromes [51][52][53], and renal cancer [54]. Recently, two reports described apoptosis induction, caspase activation and ROS production by very high concentrations (up to 40 µM) of potassium antimonyl tartrate in lymphoid tumor cell lines [55] and growth inhibition and induction of apoptosis and reactive oxygen species [56].…”
Section: Discussionmentioning
confidence: 99%
“…Arsenic trioxide (As 2 O 3 ) has shown substantial efficacy in treating both newly diagnosed and relapsed patients with acute promyelocytic leukemia (APL) [15] . Recent studies have shown that a wide variety of malignancies, including both hematological cancer and solid tumors derived from several tissue types, may be susceptible to therapy with As 2 O 3 [16][17][18][19] . These successes have prompted investigations to elucidate the mechanisms of action underlying these clinical responses.…”
Section: Introductionmentioning
confidence: 99%